More people, more food, worse water?: a global review of water pollution from agriculture - Mateo-Sagasta, Javier; Zadeh, S.M.; Turral, Hugh (CGIAR Research Program on Water, Land and Ecosystems, 2018)
Current patterns of agricultural expansion and intensification are bringing unprecedented environmental externalities, including impacts on water quality. While water pollution is slowly starting to receive the attention it deserves, the contribution of agriculture to this problem has not yet received sufficient consideration. We need a much better understanding of the causes and effects of agricultural water pollution as well as effective means to prevent and remedy the problem. In the existing literature, information on water pollution from agriculture is highly dispersed. This repost is a comprehensive review and covers different agricultural sectors (including crops, livestock and aquaculture), and examines the drivers of water pollution in these sectors as well as the resulting pressures and changes in water bodies, the associated impacts on human health and the environment, and the responses needed to prevent pollution and mitigate its risks.